Pelaksanaan Metode Storytelling dalam Meningkatkan Hasil Belajar Peserta Didik - Rani, Desti Antia; Rahman, Rini (ALSYS, 2024)
The lecture method in the teaching and learning process has been developed into the storytelling method to address the inefficiency of PAI learning at SDN 13 Sungai Betung, thereby stimulating the activity, courage, and skills of students, both individually and in groups. This research uses a qualitative method with a descriptive approach (Hanel, 2013). To select informants, the researcher uses purposive sampling technique based on specific considerations or criteria. The informants in this study are the principal, the curriculum vice principal, the Islamic Education teacher, and five fifth-grade students chosen based on class rankings and teacher recommendations. Data collection techniques include interviews, observations, and documentation, while data analysis is carried out through data reduction, data presentation, and conclusion drawing. The implementation of the storytelling method involves the preparation of visual aids such as laptops, projectors, and animated videos, as well as classroom setup. The teacher must ensure the classroom is prepared, convey the learning objectives according to the Lesson Plan (RPP) and syllabus, and use storytelling by paying attention to eye contact, facial expressions, vocal emphasis, and body movements in sync with the animated videos. The success of this method heavily relies on the preparation of media, classroom readiness, and the teacher's storytelling skills, making the learning process engaging, effective, and easy for students to understand.